Brazil's inclusion in the protection system (Revista do Tribunal Regional Federal da 3ª Região, 2017)
This paper aims to reflect on the improvement of the effectiveness of human rights in Brazil through the Brazil’s insertion in the regional protection system of human rights. For achieving this aim, present as the main reference of this phenomenon the European example, based on the application of the European Convention on Human Rights and the case law of the European Court of Human Rights, and compare the European progress with the almost non existence of Brazilian cases before the American Court of Human Rights.